Reducing of total harmonic distortion by simulating passive filters to suppress harmonic currents with the case: Faculty of Engineering Building, Universitas Kristen Indonesia Jakarta. Issue 1 (October 2021) - Prasetyo, A D T; Silalahi, E M; Stepanus, S; Widodo, B; Purba, R
Abstract: Today's electrical appliances use power electronics to save electricity. However, this equipment generates non-sinusoidal current, causing wave defect, expressed as total harmonic distortion (THD). As the %THD increases, the greater risk of equipment damage. For this reason, the research was carried out in the Faculty of Engineering Building, Universitas Kristen Indonesia Jakarta (FT UKI Jakarta) where there are many load combinations such as computers, various types of lights, laboratory equipment such as transformers, electric motors and so on. The research was conducted using quantitative method. Data collection is carried out directly in the main panel. Based on the measurement results, the calculation of the maximum load current (IL ) and short circuit (ISC ) is carried out. Through these values, it can be seen that whether the odd dominant harmonic values and orders meets the IEEE 519-2014 standards or not. Calculations and analysis of the measurement results have shown that the %THDI in the FT UKI building has not meet the standard. Therefore, it is necessary to simulate the filter design to reduce the %THDI, so that the results can meets the IEEE 519-2014 standard, which is below 5%.